Spatial concepts and architecture of nomadic camps among the steppe peoples of Inner Asia - Ferenc Zámolyi (Built Heritage)
Abstract Nomadic communities in Inner Asia and Eurasia, such as the Scythian, Turkic and Mongolian communities, have lived in wood-framed tents (yurts) for a long time, which they dismantle and assemble or simply relocate (in the case of cart-mounted tents) when changing camp sites. The allocation of space within and outside dwellings is subject to strict rules that vary from community to community. These rules have remained relatively persistent over time, but changes have occurred at certain instances. The main rules concern the spatial division within the round tent, which consists of entrance areas, areas dedicated to activities conducted by males and females, areas dedicated to housing artefacts associated with men and women and areas of high spirituality such as the fire place, threshold or roof opening. Additionally, areas with a higher or lower rank are defined where highly or less highly honoured guests, respectively, are seated. In the perception of nomadic communities, the tent itself is connected to the larger cosmos by the roof opening (roof wheel, which represents the connection with the sky) and entrance door. The orientation of the dwelling is essential, as the door always faces east (Turkic peoples) or south/southeast (Mongols). This orientation is often also repeated in the case of graves and grave monuments. Not only is the tent a strictly ordered entity, but the camp, comprising several tents, exhibits a very clearly defined structure. Kinship and social status are indicated by the placement of an individual’s tent within the larger camp. Several historical sources indicate the importance of these rules during the gathering of larger groupings of nomads (especially within the context of medieval or 18th- and 19th-century wars or other events). Khans or leaders of nomadic confederations controlled specifically ordered camps, with certain communities or troops always occupying the same locations within camps. Palace tent compounds were erected for the ruler and separated from the rest of the camp via textile screens. Dedicated officials facilitated the re-establishment of this order upon settling at a new campsite. These large camps had designated summer and winter campsites, with several stations in between. Notably, the year was spent in a cycle of moving from one site to another. These annual and seasonal cycles followed the requirements of animal herding practices. A remnant of the unique mobile palace architecture can be found today in Mongolia’s Buddhist monasteries, several of which feature large round halls resembling tents. Formerly, many monasteries were also nomadic but had become settled at fixed sites over the last approximately 100–200 years. In this study, an overview of the concepts employed by Inner Asian nomads to structure space within their dwellings and the interrelations with the wider environment is provided.